Standard Radiation Dosimetry Models: What Interventional Radiologists Need to Know - Webster, Linzi Arndt; Villalobos, Alexander; Majdalany, Bill S.; Bercu, Zachary L.; Gandhi, Ripal T.; Kokabi, Nima (Seminars in Interventional Radiology, 2021)
Thoughtful and accurate dosimetry is critical to obtain the safest and most efficacious yttrium-90 (Y90) radioembolization of primary and secondary liver cancers. Three dosimetry models are currently used in clinical practice, namely, body surface area model, medical internal radiation dose model, and the partition model. The objective of this review is to briefly outline the history behind Y90 dosimetry and the difference between the aforementioned models. When applying these three models to a single case, the differences between them are further demonstrated. Each dosimetry model in clinical practice has its own benefits and limitations. Therefore, it is incumbent upon practicing interventional radiologists to be aware of these differences to optimize treatment outcomes for their patients.
Keywords: Y90; Dosimetry; Partition Model; BSA model; MIRD model; Yttrium-90; Radioembolization